Phenolic composition, antioxidant, antimicrobial and antiproliferative activities of water caltrop pericarps extract - Yu, Haining; Shen, Shengrong (Food science & technology, 2015)
Pericarps from three different Chinese water caltrop cultivars (T. acornis Nakano., T. bispinosa Roxb., and T. quadrispinosa Roxb.) were collected and extracted using the system of methanol: water (7:3, mL:mL) and hot water. Phenolic compositions analysis indicated that gallic acid and ferulic acid contributed 74.82–99.44 mg phenolic acids/100 mg phenolic acids determined in the extraction. All water caltrop pericarps extracts (WCPE) exhibited high antioxidant capacity. WCPE showed strong in vitro inhibitory action against gram positive bacteria, gram negative bacteria, yeast and fungi. The lowest Minimum inhibitory concentration (MIC) to gram positive bacteria was 0.5 mg/mL. MTT assay and cell cycle analysis revealed that WCPE inhibited PC-3 cancer cell growth by inducing G0/G1 phase arrest without any action on RWPE-1 normal cells compared with 5-fluorouracil that showed relatively higher cytotoxicity to RWPE-1 than PC-3. •Phenolic composition of pericarps was analyzed.•WCPE exhibited high antioxidant capacity.•WCPE showed strong inhibitory action against bacteria.•WCPE inhibited cancer cell growth by cell cycle arrest not on normal cells.•WCPE inhibited PC-3 cancer cell growth by inducing G0/G1 phase arrest.